Reproduction, symbiosis, and the eukaryotic cell - Godfrey-Smith, Peter (Proc Natl Acad Sci U S A, 2015)
This paper develops a conceptual framework for addressing questions about reproduction, individuality, and the units of selection in symbiotic associations, with special attention to the origin of the eukaryotic cell. Three kinds of reproduction are distinguished, and a possible evolutionary sequence giving rise to a mitochondrion-containing eukaryotic cell from an endosymbiotic partnership is analyzed as a series of transitions between each of the three forms of reproduction. The sequence of changes seen in this “egalitarian” evolutionary transition is compared with those that apply in “fraternal” transitions, such as the evolution of multicellularity in animals.